Nanotechnology a novel approach to enhance crop productivity - Chand Mali, Suresh; Raj, Shani; Trivedi, Rohini (Biochemistry and biophysics reports, 2020)
Nanobiotechnology provides novel set of tools to manipulate and enhance crop production using nanoparticles, nanofibres, nanoemulsions, and nanocapsules. Nanomaterials provide a platform to deliver agrochemicals and various macromolecules needed for plant growth enhancement and resistance to stresses. Smart delivery of agrochemicals increases the yield by optimizing water and nutrient conditions. Another added advantage is controlled release and site-directed delivery of agrochemicals. Further enhancement in quality and quantity in agriculture can be achieved by nanoparticle-mediated gene transformation and delivery of macromolecules that induces gene expression in plants. Various types of nanomaterials have been tested so far and the results have been promising in terms of productivity and quality enhancement. •Nanotechnology products such as nanoherbicides, nanopesticides and nanobionics etc enhance crop production.•Nanobionics enhance photosynthetic activity and nitrogen metabolism in plants.